Effect of an organic shock loading on endogenous denitrification in sequential batch reactors - Rodríguez Mora, Felipe; Ferrara de Giner, Griselda (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
Véase archivo PDF